2018
DOI: 10.1145/3204460
|View full text |Cite
|
Sign up to set email alerts
|

BotMap

Abstract: The development of novel shape-changing or actuated tabletop tangible interfaces opens new perspectives for the design of physical and dynamic maps, especially for visually impaired (VI) users. Such maps would allow non-visual haptic exploration with advanced functions, such as panning and zooming. In this study, we designed an actuated tangible tabletop interface, called BotMap, allowing the exploration of geographic data through non-visual panning and zooming. In BotMap, small robots represent landmarks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 69 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…It is also possible to use self-actuated robots that can move on a flat surface and whose configuration can be used to display various graphical representations. For example, Ducasse et al [23] used a fleet of minirobots that could move independently in order to enable people with vision impairment to access panning and zooming functions on maps. Guinness et al [24] also used minirobots on a tablet for several proof-of-concept applications such as an interactive clock, a bar chart or a Braille assistant.…”
Section: Refreshable Graphicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to use self-actuated robots that can move on a flat surface and whose configuration can be used to display various graphical representations. For example, Ducasse et al [23] used a fleet of minirobots that could move independently in order to enable people with vision impairment to access panning and zooming functions on maps. Guinness et al [24] also used minirobots on a tablet for several proof-of-concept applications such as an interactive clock, a bar chart or a Braille assistant.…”
Section: Refreshable Graphicsmentioning
confidence: 99%
“…[28] highlighted the importance of providing timely feedback regarding the status of the system in a tangible interface, and ref. [23] mentioned that interruptions of object tracking sometimes led to a delay in the delivery of feedback, which could affect the user experience.…”
mentioning
confidence: 99%
“…Others focused on investigating the use of zoom operation for PVI for tangible maps [20,6,18,27,22]. Rastogi et al [20], for instance, proposed an intuitive zooming algorithm that senses the current location of the user with position sensors and provides the accurate local information either based on force or tactile feedback.…”
Section: Tactile-based Accessible Mapsmentioning
confidence: 99%
“…Through conducting a user study that compared its ability and usability with other zooming techniques (e.g., linear and logarithmic step zooming), they concluded that their technique allowed users to perform with more accuracy in locating certain objects and showed higher usability than the other two techniques. Also, Ducasse et al [6] introduced BotMap, a tangible tabletop interface, that enables PVI to explore geographical data with non-visual panning and zooming. They designed two interfaces, Keyboard and Slider, to support panning and zooming with tangibility.…”
Section: Tactile-based Accessible Mapsmentioning
confidence: 99%
“…A large body of work exists for swarm interfaces (Suzuki et al, 2022), including joysticks (Murphy, 2004), multi-touch display interfaces (Kato et al, 2009), stylus-based haptic devices (Setter et al, 2015), gesture-based interfaces (Cauchard et al, 2015), gaze-based interfaces (Erat et al, 2018), and physiological interfaces that use signals such as skin-surface EMG (Stoica et al, 2012) and EEG (Karavas et al, 2017). Tangible swarm UIs have also been demonstrated to enable a human planner to manipulate miniature robotic agents or figurines on a tabletop to interact with veridical objects or computer-generated images and maps projected onto the table surface (Le Goc et al, 2016;Ducasse et al, 2018;Kim et al, 2020).…”
Section: Related Work: Mr Emg and Gesture-based Swarm User Interfacesmentioning
confidence: 99%